Program Dakwah Jendela Islam Pada Kanal Youtube DNK TV Perspektif Teknik Produksi - Andi Fakhrullah; Andi Faisal Bakti; Tantan Hermansah; Nasichah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Jendela Islam program is one of the religious programs on UIN Jakarta's DNK TV YouTube channel. To produce Jendela Islam video content, the production crew certainly needs special techniques. As in the use of production tools (cameras, audio and lighting) so that the da'wah content can be visually accepted by the public. This study aims to analyze the production techniques of Da'wah Jendela Islam content on the YouTube channel DNK TV UIN Jakarta. This research use desciptive qualitative approach. Data collection techniques in this study put more emphasis on observation, documentation, and supplemented by literature. The theory used is the production technique of Branston and Stafford. Observations made in this study were on the production process of Jendela Islam episode 79. The results of the analysis of this study are that DNK TV only uses two lighting, namely key light and fill light. The key light used by the DNK TV crew is Godox LED 500C. The DNK TV crew also took advantage of the Fill light using the Amaran H528S LED lighting. The image composition used is two shots and medium close up. The transition technique carried out by the production crew is the cut or cutting transition.